Pemberian Terapi Musik Bahasa Inggris dalam Mengurangi Tingkat Stress Pada Lansia di Desa Bangun Rejo Kecamatan Tanjung Morawa Tahun 2024 - Zulkarnain Batubara; Rosmega Rosmega; Cristiboy Bakara; Sri Rentina (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Stress is a mental feeling disorder that often occurs in society. Starting from unhandled stress can turn into more serious. Stress can occur at all ages, especially in the elderly, the elderly are a group that is vulnerable to physical and psychosocial changes. Objective: For this reason, this community service activity aims to socialize about handling in reducing stress/stress by using United Kingdom music therapy. Method: This community service activity uses the lecture and question and answer method. The lecture method was carried out by delivering material on stress and music therapy in United Kingdom. Meanwhile, the question and answer method is carried out by asking participants about the material that has been presented. Results: The results of this community service activity were obtained that participants were able to understand and apply the material that had been delivered. Conclusion: Based on the community service activities that have been carried out, many of the participants enthusiastically received the entire series of events ranging from material presentations to question and answer interactions.